2017
DOI: 10.1103/physrevd.95.095016
|View full text |Cite
|
Sign up to set email alerts
|

Naturalness, vacuum stability, and leptogenesis in the minimal seesaw model

Abstract: The right-handed neutrinos within the type-I seesaw mechanism can induce large radiative corrections to the Higgs mass, and naturalness arguments can then be used to set limits on their mass scale and Yukawa couplings. Driven by minimality, we consider the presence of two degenerate right-handed neutrinos. We compare the limits from naturalness with the ones from the stability of the electroweak vacuum and from lepton flavor violation. Implications from neutrinoless double beta decay are also discussed and ren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 126 publications
(65 reference statements)
4
84
0
Order By: Relevance
“…Since a hierarchical spectrum of righthanded neutrinos cannot give rise to the required asymmetry at TeV scale, this mechanism gives a resonance enhancement to the lepton asymmetry by considering a very small mass splitting between the two heavy neutrinos, of the order of their average decay width. The lepton asymmetry can be found from the following formula [36,37],…”
Section: Resonant Leptogenesismentioning
confidence: 99%
“…Since a hierarchical spectrum of righthanded neutrinos cannot give rise to the required asymmetry at TeV scale, this mechanism gives a resonance enhancement to the lepton asymmetry by considering a very small mass splitting between the two heavy neutrinos, of the order of their average decay width. The lepton asymmetry can be found from the following formula [36,37],…”
Section: Resonant Leptogenesismentioning
confidence: 99%
“…3 Some recent studies on the minimal seesaw model can be found in Refs. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mass scale of these RH neutrinos is a priori unknown, the possibility of having them close to the TeV scale has received much attention in recent years, as this scenario could be directly tested in the ongoing Large Hadron Collider (LHC) experiments [6,7], as well as indirectly probed in various low-energy searches for rare lepton number violation (LNV) and/or lepton flavor violation (LFV) [8]. There are also theoretical arguments based on naturalness of the observed 125 GeV Higgs mass, which suggest the seesaw scale to be below ∼ 10 7 GeV [9][10][11], thereby making the case of low-scale seesaw more compelling.…”
Section: Introductionmentioning
confidence: 99%